Cover Crops Implementation in Mango and Longan Orchards in Battambang Province, Cambodia - Sofia Marcon; Alessandra Giuliani; Florent Tivet; Setha Rath; Rosa Roeurn; Pesith Phoeng; Veng Sar (AGRITROPICA : Journal of Agricultural Sciences, 2024)
After years of mono-cropping and farmland expansion, Cambodia faces soil degradation, deforestation, and biodiversity loss. Conservation Agriculture (CA) could improve the Cambodian situation. Among the CA approaches, permanent soil organic cover, like cover crops, decreases soil erosion, suppresses pests and diseases, and increases yields. Currently, in Cambodia, CA practices are mainly implemented in cash crops, such as soybean, corn and cassava, leaving marginal-income crops, such as fruit trees, behind. More research about CA in fruit tree production in Cambodia is needed. This study investigates cover crops’ opportunities and constraints in mango and longan orchards and farmers’ knowledge and attitude towards this practice. Mango and longan are a source of subsistence income in the country and, therefore, do generally receive less focus. Qualitative and quantitative data collection was conducted in 2022 in Battambang province. Thirty-nine semi-structured household interviews were led in nine villages of Rattanak Mondoul and Banan districts, with CA-, CT- (conventional) and CT (CA*)- (previous CA, now CT) farmers. Two Focus Group Discussions (FGDs) were led in the Sangha and Borun villages of Rattanak Mondoul districts. Key informant interviews and a literature review were used to gather data. The results showed that most farmers do not know the definition of CA. CA- and CT (CA*)-farmers are satisfied with applying cover crops and recommend CT farmers to grow them. CT farmers are willing to start growing cover crops in their orchards. The main reasons for farmers to start growing cover crops are weed presence, low soil fertility and high erosion in the orchards. Farmers have noticed an improvement in their orchards and fruit yield since they started growing cover crops. Farmers believe more training and technical support about CA and covering crops are needed. This might also attract more farmers to these approaches, increasing the adoption of CA techniques, improving Cambodian agriculture and reducing soil degradation, deforestation and biodiversity loss.